An aquifer thermal energy storage model for efficient simulations of district systems - Scalco, Elisa; Zarrella, Angelo; Maccarini, Alessandro; Alireza, Alireza (CLIMA 2022 conference, 2022)
Thermal energy storage systems are valuable assets to enable high penetration of renewable energy sources into district heating and cooling (DHC) systems. One of the main benefits of using thermal storage is that it can contribute to matching energy supply and energy demand when they do not coincide in time. Aquifer thermal energy storage (ATES) is an attractive technology to provide sustainable heating and cooling to buildings through DHC systems. In ATES systems, storage and recovery of thermal energy is achieved by extraction and injection of groundwater using wells. To calculate the energy performance of ATES, most of the studies use detailed simulation models developed using computational fluid dynamics software. However, such programs have limited capability of simulating the integration of ATES into building and district energy systems. The aim of this research study is to develop a simplified ATES model, which is suitable for coupling with building and district energy simulation programs. The model has been developed using a finite-difference approach in the MATLAB computing platform to solve the transient heat and mass transfer equations in porous media in two dimensions. The aquifer around the wells is modelled as two independent radially symmetric discs with an inner radius and an outer radius. The model has been validated by comparing predicted warm/cold well temperatures with measurements data from literature. Since the model is developed in MATLAB, it can be coupled with building energy software (such as TRNSYS, Modelica, EnergyPlus) via co-simulation.